A Return to the Beginnings of Regionalism: Shushtar New Town seen in the light of the 2nd International Congress of Architects, Persepolis, Iran 1974 - Westbrook, N.; Mozaffari, Ali (2015)
Reconstructing the city through the establishment of an organic relation between individual dwelling and community was a critical concept in the theorisation of a socially-relevant architecture in the 1960s to 1970s both in the form of treatises, and in speculative and actual projects. Underpinning all these projects was both a dismissal of the subjugation of the housing complex to larger abstract planning structures, and an apparent belief in the ability of architectural typologies to provide the scaffolding for authentic forms of social life to develop. In the Second International Congress of Architects held in Persepolis, Iran, in 1974, entitled ‘Towards a Quality of Life’, many leading international architectural theorists and practitioners debated issues pertaining to the problems inherent to social identity, human habitat, and the internal economic migration then being faced in Iran, but also familiar to Europeans since the early post-war period, and previously addressed in ‘Realist’ projects such as Ridolfi and Quaroni’s Tiburtino estate outside Rome (1949-54). Growing out of this conference was the Persepolis Declaration, a formulation of principles to underlie human settlement that was to form the basis for the 1976 Vancouver Declaration on Habitat. Among the recommendations of the Congress was the design and construction of several exemplary settlements that would form models for future housing, notably the Aga Kahn prizewinning Shushtar-No’w (Shushtar New Town), designed by the Queen’s cousin, Kamran Diba. In this paper we will examine this project in relation to the conference principles and will interrogate the following questions: can it be understood as a local search for cultural traditions and essences, or for international precedents and narratives that can be reshaped in a local context? How are the two negotiated?